Pengaruh Implementasi Sistem Informasi Akuntansi, Pemanfaatan Teknologi Informasi dan Kompetensi Sumber Daya Manusia Terhadap Kinerja UMKM (Studi Empiris: Rokan Hulu) - Syahida, Aztyara; Azlina, Nur; Humairoh, Fitri (Jurnal Akuntansi Kompetif, 2025)
Abstract: The purpose of this study is to analyze the impact of the implementation of accounting information systems (AIS), the use of information technology (IT) and human resource competencies (HR) on the performance of micro, small and medium enterprises (MSMEs). A total of 100 MSMEs were sampled with data from questionnaires distributed to MSMEs in Rokan Hulu Regency, Riau Province. Multiple linear regression is the method used with the help of SPSS software version 25. The results of the study explain that the implementation AIS and HR had a significant impact on the performance of MSMEs. However, the use of IT doesn’t show a significant impact on the performance of MSMEs.